Implementation Of Quality Audit In Realizing Good University Governance At The University Muhammadiyah Parepare - Darmawan, Darmawan; Alam, Syamsu; Zakaria, Junaidin (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
Education Quality is the level of conformity between the implementation of higher education with Higher Education Standards consisting of National Higher Education Standards and Higher Education Standards set by universities. The objectives in this study are: To determine the adequacy of regulations owned as guidelines for the implementation of Higher Education operational activities, To find out the existence of national standards used as a reference in carrying out Higher Education operational activities, To find out the existence of Higher Education standards as a reference for the implementation of operational activities adapted from local, national and international and to find out the quality audit process carried out by UMPAR thus guarantees that the implementation of PT operational activities is in accordance with the regulations owned. The research approach used is a qualitative approach, the data analysis technique used is qualitative data analysis with three lines of analysis such as data reduction, data presentation, and conclusions. The results in this study are 1) The implementation of education at the University of Muhammadiyah Parepare still refers to the policies of the central government and the Muhammadiyah organization. 2) The University of Muhammadiyah Parepare needs to prepare itself well by developing a strategic plan to support the implementation of operational activities in facing future challenges Implementation of a program and activity for the next 5 years. 3) Internal Quality Assurance Standard Policy of the University of Muhammadiyah Parepare covers all aspects of higher education implementation with the main focus on aspects of education, research, community service, and Al Islam-Kemuhamadiyahan, The results of the implementation of the internal quality assurance system with the form of evaluation of the PPEPPP model are readiness to implement accreditation for study programs within the University of Muhammadiyah Parepare.